Steinbeck's New York Apartment - Philip O. Roedel:::Creator::::::::::::
John Steinbecks's apartment dressing room on the 34th Floor of 190 East 72nd Street in New York City From the caption: Decorator John James Fisher carried the restful blue-and-olive print throughout the bedroom [see photo number 1-288] and dressing room...but gave it subtle, eye-amusing variety by changing its textures. It is used flat as wallcovering and on chair cushions, quilted in the bedspread, and sheer in the window curtaining. Then--most masterful match of all--the fabric was laminated into the rigid plastic from which the Venetian blinds were made.